Bioanalytical method validation for the determination of opiates, opioids and its metabolites in forensic interest samples, by gas chromatography-mass spectrometry (Revista de Investigaciones Universidad del Quindío, 2015)
Due to the increase in reported cases of crimes such as, sexual offenses and theft in persons placed in a state of helplessness committed under the infl uence of drugs of abuse and evidences of accidental intoxication, suicide and homicide associated to the consumption of these, is necessary the development of analytical technical, selective, sensitive and reliable for determination of the drugs in biological samples in cases of forensic interest. Was validated a method for determination of morphine, codeine, 6-acetylmorphine and methadone, in urine and blood. The percentages of recovery were higher than 56 y 63% to all the analytes evaluated in urine and blood respectively. The calibration curves was linear with correlation coeffi cients higher than 0.98, within the dynamic range associated to the toxic concentrations or lethal reported in the literature. The CMD and CMC of each analyte were determined statistically from the constructed calibration curves. The precision had coeffi cients of variation lower than 24% for analytes. Was obtained for codeine in urine 78.9% of positive predictive value and blood 100%, as morphine in urine.The development method was applied successfully for resolution the forensic cases of traffi c accidents, deaths on study, determination of non-alcoholic drunkenness and suicide or accidental poisoning.
Keywords: Opiates; opioids; blood; urine; gas chromatography-mass spectrometry